Implementation Of Rewards And Punishments In Increasing Student Learning Motivation Class IV B SDN 7 Sambik Bangkol - Sumarni, Sumarni; Habiburrahman, Lalu; Mulyono, Ana (Peneliti.net, 2025)
This study was motivated by the low learning motivation of students in class IV B SDN 7 Sambik Bangkol in participating in the learning process. This can be seen from the lack of active participation of students during learning activities, such as not doing assignments, often playing when the teacher explains, and often coming late. Based on these problems, the purpose of this study is to find out the implementation of rewards and punishments in increasing student learning motivation and its impact on student behavior. This research uses a qualitative approach with descriptive methods. The data collection techniques used include observation, interviews, questionnaires, and documentation. The research subjects consisted of class IV B students, homeroom teachers, and school principals. Data were analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the application of rewards such as verbal praise, giving stickers, and simple gifts can increase students' enthusiasm for learning. Punishments that are educational in nature such as reprimands and additional assignments are also effective in shaping student discipline. There are changes in student behavior in a more positive direction after the implementation of the reward and punishment system, such as increased attendance, discipline, and activeness in learning. This research suggests that teachers should be more consistent in applying rewards and punishments fairly and sustainably, as well as involving students in the implementation of rewards and punishments. such as increased attendance, discipline, and activeness in learning. This study suggests that teachers should be more consistent in applying rewards and punishments fairly and sustainably, and involve all subject teachers in the system for more optimal results.